Accelerated Skeletal Maturation in Disorders of Retinoic Acid Metabolism: A Case Report and Focused Review of the Literature - Nilsson, O.; Isoherranen, N.; Guo, M. H.; Lui, J. C.; Jee, Y. H.; Guttmann-Bauman, I.; Acerini, C.; Lee, W.; Allikmets, R.; Yanovski, J. A.; Dauber, A.; Baron, J. (Hormone and Metabolic Research, 2016)
Nutritional excess of vitamin A, a precursor for retinoic acid (RA), causes premature epiphyseal fusion, craniosynostosis, and light-dependent retinopathy. Similarly, homozygous loss-of-function mutations in CYP26B1, one of the major RA-metabolizing enzymes, cause advanced bone age, premature epiphyseal fusion, and craniosynostosis. In this paper, a patient with markedly accelerated skeletal and dental development, retinal scarring, and autism-spectrum disease is presented and the role of retinoic acid in longitudinal bone growth and skeletal maturation is reviewed. Genetic studies were carried out using SNP array and exome sequencing. RA isomers were measured in the patient, family members, and in 18 age-matched healthy children using high-performance liquid chromatography coupled to tandem mass spectrometry. A genomic SNP array identified a novel 8.3 megabase microdeletion on chromosome 10q23.2–23.33. The 79 deleted genes included CYP26A1 and C1, both major RA-metabolizing enzymes. Exome sequencing did not detect any variants that were predicted to be deleterious in the remaining alleles of these genes or other known retinoic acid-metabolizing enzymes. The patient exhibited elevated plasma total RA (16.5 vs. 12.6±1.5 nM, mean±SD, subject vs. controls) and 13-cisRA (10.7 nM vs. 6.1±1.1). The findings support the hypothesis that elevated RA concentrations accelerate bone and dental maturation in humans. CYP26A1 and C1 haploinsufficiency may contribute to the elevated retinoic acid concentrations and clinical findings of the patient, although this phenotype has not been reported in other patients with similar deletions, suggesting that other unknown genetic or environmental factors may also contribute.
Keywords: retinoic acid; bone age; growth plate; growth